2014
DOI: 10.3791/50682
|View full text |Cite
|
Sign up to set email alerts
|

3D-Neuronavigation <em>In Vivo</em> Through a Patient's Brain During a Spontaneous Migraine Headache

Abstract: A growing body of research, generated primarily from MRI-based studies, shows that migraine appears to occur, and possibly endure, due to the alteration of specific neural processes in the central nervous system. However, information is lacking on the molecular impact of these changes, especially on the endogenous opioid system during migraine headaches, and neuronavigation through these changes has never been done. This study aimed to investigate, using a novel 3D immersive and interactive neuronavigation (3D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…In humans, similar changes in FC where found in high frequent episodic migraineurs between PAG and PFC (Solstrand and Dahlberg et al, 2018). We previously demonstrated an increase in μ-opioid receptor-mediated neurotransmission in PAG and mPFC during a spontaneous EM attacks and allodynia (DaSilva et al, 2014a, DaSilva et al, 2014b), when compared to the interictal phase. Herein, when ictal CM attacks where compared with HCs during thermal challenge, we noticed that μ-opioid system activity was also increased in the thalamus and caudate, confirming that important brain regions generally involved in sensory processing and modulation of pain are also affected at the circuit level, facilitating ascending cephalic pain inputs with inefficient inhibitory pain modulatory responses to external stimuli (Jia and Yu., 2017; Wunderlich et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In humans, similar changes in FC where found in high frequent episodic migraineurs between PAG and PFC (Solstrand and Dahlberg et al, 2018). We previously demonstrated an increase in μ-opioid receptor-mediated neurotransmission in PAG and mPFC during a spontaneous EM attacks and allodynia (DaSilva et al, 2014a, DaSilva et al, 2014b), when compared to the interictal phase. Herein, when ictal CM attacks where compared with HCs during thermal challenge, we noticed that μ-opioid system activity was also increased in the thalamus and caudate, confirming that important brain regions generally involved in sensory processing and modulation of pain are also affected at the circuit level, facilitating ascending cephalic pain inputs with inefficient inhibitory pain modulatory responses to external stimuli (Jia and Yu., 2017; Wunderlich et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…So far, the only direct investigation of endogenous μ-opioid activation in vivo was done with positron emission tomography (PET) in EM patients with allodynia. This study showed a decrease in μOR non-displaceable binding potential (BP ND ) with [ 11 C]carfentanil (DaSilva et al, 2014a). μOR BP ND is a selective measurement of μOR availability in vivo , and its immediate decrease during EM headache attack (ictal phase) and allodynia mostly suggested the existence of a transitory increase in ictal activation of endogenous μ-opioid neurotransmission in the periaqueductal gray matter (PAG) and medial prefrontal cortex (mPFC), rather than a sharp change in the number of μOR (DaSilva et al, 2014b; Nascimento et al, 2014).…”
Section: Introductionmentioning
confidence: 94%
“…5658 Indicating that there is endogenous opioid release during a migraine attack, these studies have shown reduced mu-opioid non-displaceable binding potential in the cingulate cortex, nucleus accumbens, thalamus, periaqueductal gray, and medial prefrontal cortex. 56, 57 …”
Section: Functional Imaging Studies During a Migraine Attackmentioning
confidence: 99%
“…However, step by step, they are contributing to dental education, research, and treatment. For example, data from brain imaging of patients during pain can be visualized by students in virtual reality to have a more immersive educational experience (DaSilva et al 2014). The same applies with orthognathic surgical simulation methods when combined with traditional records, showing positive attitudes from the students toward higher-fidelity tools concerning visualization, manipulation, and enjoyment of the task (Sytek et al 2021).…”
Section: Digital Dentistry For Diagnosis and Treatmentmentioning
confidence: 99%